Gender-differentiated farmers' perception of climate risk and its impact, access to climate information, and adaptation strategies in Senegal - Kumar, Shalander; Pramanik, Soumitra; Yessoufou, Adjani Nourou-Dine; Gondwe, Therese; Worou, Nadine; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
AICCRA (Accelerating Impacts of CGIAR Climate Research in Africa), started in 2021 in six (6) African countries (Ethiopia, Kenya, Zambia, Ghana, Mali, Senegal) with the ambition to build technical, institutional and human capacities needed to improve the transfer of climate-related information, decision-making tools and technologies in support of climate change efforts. The present study uses the AICCRA-Senegal baseline data to understand the gender-differentiated farmers' perception of climate risk and its impact, access to climate information, and adaptation strategies. The study covers 514 households in three regions of Senegal, namely Kaffrine, Louga and Thies. The analysis shows that though the in terms of knowledge and understanding about climate change there is no significant deviation between adult men and women respondents, but dissemination efforts on climate information services and capacity development related to CSA the significantly wide gap exists between men and women farmers. The climate related literacy among the women respondents in the study regions was found that more than 80% of both women and men were aware of climate change. The majority of farmers both men and women perceived a strong to the very strong adverse impact of climate change on crop production in terms of yield and quality loss, water scarcity, new pests and diseases and the impact on soil health. Livestock production has been impacted by the adverse effects of climate change in terms of a decrease in milk yield, increased animal diseases, reduced feed, fodder and water availability for animals use. When it comes to access of climate-related information and capacity building on climate adaptation, the rate of participation of women members of the farm household was very low ( 5%). Although we found that more than 80% of the women respondents have perceived knowledge about climate change and its impacts and they form about 50% of the farm family workforce, their access to climate information and knowledge is very little. We conclude that poor integration of farm women into the climate adaptation programs is likely to have poor outcomes. Any climate adaptation program cannot achieve its objectives unless it equally builds the capacity of farm women for climate adaptation. This study has helped AICCRA-Senegal to make its interventions on improving climate information services and climate-smart agriculture more gender sensitive.